2001
DOI: 10.1016/s0731-7085(00)00562-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of myocardial norepinephrine in freely moving rats using in vivo microdialysis sampling and liquid chromatography with dual-electrode amperometric detection

Abstract: Myocardial norepinephrine (NE) is considered a meaningful parameter for estimation of cardiac function. Long lasting changes in myocardial NE appear to be not only a consequence of pathologic processes in the myocardium, but may be a factor responsible for some diseases (e.g. increased propensity for arrhythmias or negative effect on left ventricular contractility in congestive heart failure). In this respect monitoring of myocardial NE is of great importance. A microdialysis sampling technique coupled with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…A related finding is the depletion of NE that occurs in all heart chambers following cardiac transplantation (Mohanty et al, 1986). In order to better understand SNS dysfunction in cardiovascular disease, it is important to have a reliable method for monitoring NE content, and its metabolites, both during disease development and in the chronic disease state (Berquist et al, 2002;Gilinsky et al, 2001;Makoto, 2006;Nikolajsen and Hansen, 2001;Peaston and Weinkove, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related finding is the depletion of NE that occurs in all heart chambers following cardiac transplantation (Mohanty et al, 1986). In order to better understand SNS dysfunction in cardiovascular disease, it is important to have a reliable method for monitoring NE content, and its metabolites, both during disease development and in the chronic disease state (Berquist et al, 2002;Gilinsky et al, 2001;Makoto, 2006;Nikolajsen and Hansen, 2001;Peaston and Weinkove, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…HPLC with electrochemical detection is the most commonly used method for quantitative determination of biogenic amines and metabolites in tissue, plasma and urine (Cheng and Kuo, 1995;Chi et al, 1999;Davis et al, 1981;Gilinsky et al, 2001;Machida et al, 2006;Patel et al, 2005;Sabbioni et al, 2004;Sastre et al, 2004;Unceta et al, 2001). Another informative, but less used technique, for bioanalyte monitoring in tissue is capillary electrophoresis (CE) (Dillon and Sears, 1998;Markuszewski et al, 2003;Paxon et al, 2005;Qurishi et al, 2002;Shou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gilinsky et al [26] used LC with ECD to measure myocardial norepinephrine (NE) and reported detection limits of 10 pg/mL in 20 mL MD sample sizes. NE has been closely related to changes in cardiac functioning.…”
Section: Detectors Coupled With Hplc Analysismentioning
confidence: 99%
“…This technique has been employed extensively for pharmacokinetic and pharmacodynamic studies as well as for drug delivery. Microdialysis has been used to monitor drugs and other biologically important compounds in virtually every tissue and organ in the body, including liver [1,2] , heart [3,4] , skin [5,6] , blood [7,8] , placenta [9] , stomach [10,11] , ear [12] , and brain [13,14] .…”
Section: Introductionmentioning
confidence: 99%